Цифровізація і технологічна трансформація як відповідь на сучасні глобальні виклики та шлях до формування стійких конкурентних переваг національних підприємств - Ткаченко, А.М.; Маслов, Д.Г. (Економічний вісник Донбасу, 2025)
У статті досліджуються питання впливу цифровізації, діджиталізації та технологічних досягнень сучасної науки на рівень конкурентоспроможності національних підприємств. Окремо розглядаються шляхи, за допомогою яких національні підприємства можуть досягти стійких конкурентних переваг як у межах національної економіки, так і за її кордонами. Актуальність дослідження зумовлена необхідністю ширшого вивчення шляхів забезпечення конкурентних переваг у сучасних умовах завдяки використанню новітніх технологій. В умовах глобалізації дедалі більше країн та їхніх підприємств активно впроваджують сучасні технології, вбачаючи в цьому значні можливості. Для України це набуває особливого значення, оскільки з огляду на сучасні виклики для держави та національних виробників застосування новітніх технологій є не лише шляхом досягнення стійкості, а й необхідною умовою для виживання. У дослідженні аналізується вплив цифровізації та сучасних технологій на рівень конкурентоспроможності підприємств, а також виокремлено можливості, які може отримати національний виробник від їхнього впровадження у господарську діяльність. Під час роботи використано наукові матеріали, статті та тези, опубліковані у провідних українських та іноземних фахових виданнях. Для забезпечення достовірності результатів проведено оцінку надійності джерел (аналіз авторитетності видань та відповідності інформації первинним джерелам), здійснено перехресну перевірку показників і оцінку узгодженості статистичних даних. The article examines the impact of digitalization and technological advancements of modern science on the competitiveness of national enterprises. In addition, it considers the ways through which enterprises can achieve more sustainable competitive advantages both within the national economy and beyond. The relevance of the study lies in the need for a broader exploration of strategies for gaining stable competitive advantages under current conditions through the use of advanced technologies. In the context of globalization, more countries and their enterprises are introducing modern technologies, seeing in them significant opportunities. For Ukraine, this issue is particularly urgent: given the current challenges facing the country and its enterprises, the adoption of new technologies is not only a way to achieve resilience but also an essential condition for survival. The main purpose of the article is to analyze the opportunities and provide practical recommendations regarding the use of modern technologies in the activities of national enterprises. The research investigates the influence of digitalization and technological innovations on competitiveness and highlights the benefits that domestic producers may obtain from their implementation. The paper also examines the circumstances in which Ukrainian enterprises and the state currently operate, their awareness of the potential of technology, as well as the risks of ignoring timely adoption. The study is based on scientific materials, articles, and theses published in leading Ukrainian and foreign academic journals. To ensure data reliability, the author conducted a source credibility assessment (evaluating journal authority and compliance with primary sources), cross-checked data from different sources, and assessed the consistency of statistical information. Within the methodology, primary documents (laws, official reports) were used to validate facts. These measures significantly improved the accuracy of the results and reduced the likelihood of bias or inconsistencies. The research applied a combination of quantitative and qualitative methods. Factor and cluster analysis were employed to identify key trends in competitiveness. Descriptive methods (sorting, filtering, visualization) were used to structure large datasets, while textual analysis helped to detect thematic trends in scientific publications.